Interpreting Religious Tolerance in the Qur’an through Thematic Exegesis: Insight for Contemporary Multicultural Societies - Silvinatin Al Masithoh; Abd. Kholid (JURNAL AT-TURAS, 2026)
This study examines the concept of religious tolerance in the Qur'an through a thematic interpretation approach and analyzes its implications in contemporary society. Religious tolerance is a crucial issue amid religious diversity, which is a global reality, including in Indonesia as a highly diverse country. However, there is still a gap in understanding how the Qur'an comprehensively views interfaith relations, which often leads to partial and contradictory interpretations. This study attempts to answer the following questions (1) How is the concept of religious tolerance in the Qur'an according to thematic interpretation studies? (2) What are the fundamental principles of religious tolerance contained in the Qur'an? (3) What are the implications of the concept of religious tolerance in the Qur'an for contemporary society? (4) How is the concept of religious tolerance practically implemented in the context of Indonesia as a multicultural country? This study uses a qualitative method with a library research approach, collecting data from primary sources in the form of tafsir books and the Qur'an, as well as secondary sources in the form of journals, books, and related scientific articles. Data analysis is carried out using content analysis and comparative techniques to compare the various views of exegetes. The results of this study are expected to contribute to a holistic and contextual understanding of religious tolerance according to the Qur'an, while offering practical solutions for realizing peaceful and mutually respectful religious life amid the plurality of Indonesian and global societies.